Influence of EFL Teachers’ Self-Assessment on Their Self-Regulation and Self-Efficacy - Huang, Qian (Frontiers in Psychology, 2022)
This review aimed at investigating the related studies on English as a Foreign Language (EFL) teachers’ self-assessment and its role in their self-efficacy and self-regulation. Earlier investigations have proved that teacher self-assessment was significantly correlated with self-regulation. Moreover, studies showed that self-assessment and self-regulation enabled teachers to consider their teaching effectiveness, and they were important components of formative assessment. Earlier studies showed that self-assessment raised learner awareness and increased self-efficacy significantly through the improvement of mastery experiences. Furthermore, the study presented the implications and future directions of this line of research for different people, such as EFL teachers, teacher educators, and foreign language scholars. The ideas can improve their awareness of teacher self-assessment, self-regulation, and self-efficacy in educational contexts.